Promoting Research in the Teaching-Practice of the Modern Language Licenciatura Programs - Liliana del Pilar Gallego Castaño; Josefina Quintero Corzo; Carmen Tulia Zuluaga Corrales (Asociación Colombiana de Profesores de Ingles, 2016)
This paper presents a research process that should be applied by teacher-trainees and advisors for their own educational activities. The most relevant aspect of a quantitative or qualitative research process is to identify personal meanings about pedagogical contexts in which educators are situated. The teacher as a researcher would identify educational needs in order to improve and qualify his/her action. Teachers and students may be able to identify the broad problem areas that are most closely related to their interests and professional goals. Research becomes more than informing; it is in fact transforming.